Los parientes del diputado: las redes familiares del caciquismo liberal - Juan Antonio Inarejos Muñoz (Nuevo mundo - Mundos Nuevos, 2008)
The aim of this work is to analyse from the significance of family networks, the basic focus of the patronage system, that have in the clienteles organized around Political parties and institutions. In the social networks conjugated around representative power, family relationships were set up as a platform to organise the electoral patronage. The course of elections is a privileged scene to reduce the political use of family networks, which was one of the most important components of the political parties, and their relations with local and state powers. The analysis has been made, fundamentally, with private documentation, in close relation with the discriminatory condition of the patronage system, and imbued with new interpretations that revalue the social component to interpret the general design of patronage system.